Strengthening resilience in school – a narrative examination about how teachers promote resilience by providing social support - Diers, Manuela (Berdyansk State Pedagogical University, 2016)
The article presents a recent study on the question of how young people suffering from psychological risks in their environment recreate social support from teachers in their narratives and what kind of role teachers’ social support plays for children and young adults living at high risk and for strengthening resilience. It points out that teachers can initiate creative metamorphosis of biographical identity to help overcome trajectories of suffering. The link between biographical and resilience research is discussed on the basis of Marica’s case. One key result is the importance of teachers in the role of significant others, a position which enables them to strengthen resilience. A constructive, trustful and approving teacher-student relationship is the basis for the resilient development of children at high risk.
Keywords: resilience; school; support; biographical research